ORGANIC TRASH MANAGEMENT TOURISM ACCOMMODATION AT MAIMAGOT ORGANIC FARM IN ABIANBASE VILLAGE, BERKATAN, BADUNG REGENCY - Anak Agung Any Sutraningrum (UHN IGB Sugriwa Denpasar, 2023)
The research conducted aims to analyze the management of organic trash for tourism accommodation carried out by the Maimaggot organic farm. The organic trash generated by the restaurant kitchen of the Four Seasson Sayan and Alam Group Ubud hotels is managed by the Maimaggot organic farm so that it becomes a product that has economic value. Products that can be produced from organic trash that have been properly managed include maggot as an alternative feed for chickens, ducks, birds and fish and managed to become compost products. According to information from the manager of the Maimaggot organic farm , efforts to deal with organic trash need collaboration with various parties, especially in the early stages of sorting trash from its source so as to produce good quality maggot feed. The results of this study are expected that tourism accommodation managers understand the importance of managing organic trash properly so that it will not pollute the hotel environment